IMPLIKASI POSITIF SERTIFIKAT HALAL BAGI PELAKU UMKM DI DESA BANTARSARI - Muhammad Zainul Mustova; Azhar Ramadan; Siti Risalatul Muawanah; Tazkia Azzahra; Muhammad Tanto Herlambang; Muhamad Hasan Muazis (STIT Sirojul Falah Bogor, 2025)
The aim of this study is to identify the increase in the value of halal certification for Micro, Small and Medium Enterprises (MSMEs) in Bantarsari Village. Halal issues have become a global phenomenon which is reflected in the existence of halal certification institutions in various parts of the world. This research uses a qualitative descriptive method through a review of relevant literature and observation of the implementation practices of the halal guarantee system in Indonesia. Data was collected from various sources such as journals, books, magazines, newspapers, electronic media including the official LPPOM MUI website, as well as through personal communication with competent sources. Research findings show that halal product certification has a positive impact in building a halal-focused business environment in Bantarsari Village. From a consumer perspective, halal certification provides protection, guarantees, information about the halalness of products, and functions as an ethical tool in business.